"Experiential Learning by Accident: Piloting the Moral Courage Project". (22nd December 2021) - Pruce, Joel R.
Abstract: A team from the University of Dayton, consisting of undergraduate students, a faculty facilitator, and practitioner partners, conducted an innovative oral history project documenting the experiences of ordinary people who lived through the unrest following Michael Brown's death in 2014. The Moral Courage Project sought to investigate the spectrum of stories from Ferguson that failed to fit into the extreme and polarized narratives emerging from mainstream media coverage and were, therefore, overlooked. With the testimonies collected, the team produced a multimedia exhibit featuring portraits and audio materials, as well as a podcast series and a storytelling website. This paper describes the origins and outlines of this unique program in the context of an experiential learning framework. While accounting for the project's successes, the author also reflects on ways that student outcomes could have been improved had greater focus been placed on experiential learning processes and structures.